English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

1. (2,0) and (5,9)
2. (5,-1) and (-2,3)
3. (-5,-2) and (-7, -1)
4. (2,-8) and (1,0)

answers:
A. sqrt 145
B. sqrt65
C. 5
D. sqrt 13
E. 3sqrt10
F. sqrt5
G. sqrt73
H. sqrt43

2007-01-20 13:12:29 · 3 answers · asked by hans d 1 in Science & Mathematics Mathematics

3 answers

1. = root ( (5-2)^2 + (9-0)^2)
= root (9+81)
= root(90)
= 3 root 10
So it is E

2. = root[(-2-5)^2 + ((3-(-1))^2]
= root ((-7)^2 + 4^2)
= root (49 + 16)
= root 65
So B

3. = root [((-7 - (-5))^2 + (-1 -(-2))^2]
=root ((-2)^2 + (-1 +2)^2)
= root (4 +1)
= root 5
So choose F

4. = root[(1-2)^2 + (0-(-8))^2]
= root [ (-1)^2 + 8^2)
= root [1 + 64]
= root 65
So choose B

2007-01-20 13:41:20 · answer #1 · answered by Wolfshadow 3 · 0 0

D = sqrt((x2 - x1)^2 + (y2 - y1)^2)

1.)
(2,0) and (5,9)
D = sqrt((5 - 2)^2 + (9 - 0)^2)
D = sqrt(3^2 + 9^2)
D = sqrt(9 + 81)
D = sqrt(90)
D = sqrt(9 * 10)
D = 3sqrt(10)
ANS : E.) 3sqrt(10)

--------------------------------------

2.)
(5,-1) and (-2,3)
D = sqrt((-2 - 5)^2 + (3 - (-1))^2)
D = sqrt((-2 + (-5))^2 + (3 + 1)^2)
D = sqrt((-7)^2 + 4^2)
D = sqrt(49 + 16)
D = sqrt(65)
ANS : B.) sqrt(65)

--------------------------------------

3.)
(-5,-2) and (-7,-1)
D = sqrt((-7 - (-5))^2 + (-1 - (-2))^2)
D = sqrt((-2)^2 + 1^2)
D = sqrt(4 + 1)
D = sqt(5)
ANS : F.) sqrt(5)

-------------------------------------------------

4.)
(2,-8) and (1,0)
D = sqrt((1 - 2)^2 + (-8 - 0)^2)
D = sqrt((-1)^2 + (-8)^2)
D = sqrt(1 + 64)
D = sqrt(65)
ANS : B.) sqrt(65)

So 2 of these problems have the same answer.

2007-01-20 21:52:36 · answer #2 · answered by Sherman81 6 · 0 0

1-E
2-B
3-A
4-B

2007-01-20 21:19:31 · answer #3 · answered by bruinfan 7 · 0 0

fedest.com, questions and answers